Gardner Denver - Elias, Jaan, (SAGE Business cases., 2020)
As KKR, a private equity firm, prepared to take Gardner-Denver, one of its portfolio companies, public in mid-2017, a discussion arose on the Gardner-Denver board about the implications of granting approximately $110 million in equity to its global employee base as part of its innovative "broad-based employee ownership program".